Mass Shooting in Marjory Stoneman Douglas High School as Seen in “Parkland: Inside Building 12” Documentary Film - Makassar, Maulana Rabbani; Ahsani, Nizam (CV. Tripe Konsultan, 2024)
This research is entitled “Mass Shooting in Marjory Stoneman Douglas High School as Seen in “Parkland: Inside Building 12” Documentary Film.” Mass shooting in America, especially in schools is widespread. The issue of gun law and gun ownership in America has become a matter of great concern. Individuals who have reached the age of 18 can easily purchase firearms from a retail without any prerequisites. The research was conducted to describe the motive of the perpetrator doing the shooting and the impact of the shooting on the victims of the Parkland shooting. The research method applied in this research was descriptive qualitative taking the main data the documentary film, videos on YouTube, and interviews from the internet. The behaviourism theory by John Broadus Watson and the Labelling Theory by Howard Saul Becker were applied, as well as the Trauma Concept by Judith Lewis Herman. The finding showed that the perpetrator, Nikolas Cruz has struggled to socialise with her friends from early life, got humiliated and felt rejected by his surroundings. These symptoms led him to trauma and strange behavior. These symptoms caused him to carry out the school shooting at Marjory Stoneman Douglas High School. On the other hand, the victims of the Parkland Shooting suffered trauma as can be seen from their reactions and what they told the director of the documentary film. The parents’ victims were also traumatized.